2019
DOI: 10.1364/ome.9.002748
|View full text |Cite
|
Sign up to set email alerts
|

Pulse-induced transient blue absorption related with long-lived excitonic states in iron-doped lithium niobate

Abstract: Transient absorption is studied in Fe-doped lithium niobate single crystals with the goal to control and probe a blue absorption feature related with excitonic states bound to Fe Li defect centers. The exciton absorption is deduced from the comparison of ns-pump, supercontinuumprobe spectra obtained in crystals with different Fe-concentration and Fe 2+/3+ Li-ratio, at different pulse peak and photon energies as well as by signal separation taking well-known small polaron absorption bands into account. As a res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
11
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(14 citation statements)
references
References 30 publications
2
11
0
1
Order By: Relevance
“…Indeed, room-temperature transient absorption measurements on a series of Mg-doped and nominally pure LN samples by Conradi et al [26] also concluded that the primary signal at 785 nm stems from Nb 4+ free small polarons. Furthermore, subsequent work only found a secondary relatively weak and slow decay that most likely results from the recombination of self-trapped excitons pinned at various defects [29,31]. As shown in Figure 1, a single KWW function provides a satisfactory fit to our low-temperature data.…”
Section: Combining the Decay Of Lithium Niobate's Induced Absorption mentioning
confidence: 58%
See 1 more Smart Citation
“…Indeed, room-temperature transient absorption measurements on a series of Mg-doped and nominally pure LN samples by Conradi et al [26] also concluded that the primary signal at 785 nm stems from Nb 4+ free small polarons. Furthermore, subsequent work only found a secondary relatively weak and slow decay that most likely results from the recombination of self-trapped excitons pinned at various defects [29,31]. As shown in Figure 1, a single KWW function provides a satisfactory fit to our low-temperature data.…”
Section: Combining the Decay Of Lithium Niobate's Induced Absorption mentioning
confidence: 58%
“…The transient near infra-red absorption in LN is primarily due to small polarons [6,28]. Other optical phenomena are also associated with self-trapped charge carriers and excitons [29][30][31][32][33] We explore the transient absorption from 10 −7 to 10 5 s for temperatures between 45 K and 225 K. A simple model enables us to relate the observed decay rate of the absorption to the temperature-dependent small-polaron jump rate. Analysis of the small-polaron jump rate through the observed temperature range yields plausible estimates of the activation energy for small-polaron hopping and distinctively, the characteristic atomic-vibration frequency.…”
Section: Introductionmentioning
confidence: 99%
“…In their revised excitation and relaxation model, different excitation paths entailing pinned-STE formation are proposed, which have recently been confirmed experimentally for Fe-doped crystals 30 . One of these paths is the band-to-band generation of electron-hole-pairs subsequently forming self-trapped excitons, which in turn migrate through the crystal until they are pinned on a defect.…”
mentioning
confidence: 79%
“…In this work we critically summarize and partially reinterpret existing experimental results on UV-excited luminescence, time-resolved PL and TA in undoped and Mg or Fe-doped LiNbO 3 crystals taking into account also recent crucial data of Messerschmidt et al [28] on the selective excitation of long TA. We also present better resolved, fs-pulse-induced PL results, together with detailed temperature dependences of the reinterpreted parameters.…”
Section: Introductionmentioning
confidence: 90%